2001
DOI: 10.1007/s004170100343
|View full text |Cite
|
Sign up to set email alerts
|

Internal limiting membrane ablation in pig eyes with the Er:YAG laser under perfluorodecalin

Abstract: Removal of the ILM by Er:YAG laser is possible in vivo. However, the variability of the laser effects calls for further improvement such as a reliable indicator of ablation depth. In any case, any damage to the retina was lesser than that produced by microforceps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Principal limitations in the ablation precision achievable with free-running Er:YAG-laser pulses arise from the fact that the laser pulse duration (400 microseconds in this study) is considerably longer than the time required for heat diffusion out of the layer in which the laser energy is absorbed [37]. Even through the optical penetration depth at such radiant exposures is only about 1 mm, thermal diffusion results in heating of a thicker layer [33].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Principal limitations in the ablation precision achievable with free-running Er:YAG-laser pulses arise from the fact that the laser pulse duration (400 microseconds in this study) is considerably longer than the time required for heat diffusion out of the layer in which the laser energy is absorbed [37]. Even through the optical penetration depth at such radiant exposures is only about 1 mm, thermal diffusion results in heating of a thicker layer [33].…”
Section: Discussionmentioning
confidence: 92%
“…D'Amico [21] and associates created full thickness retinal defects in enucleated rabbit eyes using 20 additive pulses and a radiant exposure of 3.6 J/cm 2 . Recently, it was shown that the Er:YAG laser in combination with perfluorocarbon liquid produced precise ablation of pig retina concluding that this technique provides safe removal of epiretinal membranes [22,37,38]. Perfluorocarbon liquid was used, because it served as an excellent transmitting agent for infrared radiation [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative methods to circumvent the restricted viral transduction imposed by the ILM in primates have been suggested including enzymatic digestion of the ILM with a nonspecific protease (Dalkara et al 2009; Zhang, Tuffy, et al 2021), photodisruption (Peynshaert et al 2022; Janknecht et al 2001) or sub-ILM injection (Boye et al 2016). Enzymatic digestion has the advantage of not requiring surgery, but this has not been attempted in NHPs where the ILM is thicker than in small animal models.…”
Section: Discussionmentioning
confidence: 99%